SAT0510 Effect of pharmacological and non-pharmacological therapy of obesity on the clinical manifestations of osteoarthritis. (15th June 2017) - Strebkova, E; Alekseeva, L
Abstract : Background: Osteoarthritis (OA) and obesity are inter-related and most challenging conditions for the public health, leading to significant deterioration in quality of life. Obesity is considered to be associated with the incidence and progression of OA, thus weight loss is of paramount importance in OA management. Objectives: To evaluate the efficacy of pharmacological and non-pharmacological therapy of obesity in pts with knee OA. Methods: The study included 50 female pts aged 45–65 years with knee OA, Kellgren-Lawrence stage II-III, and obesity (BMI>30kg//m 2 ). Pts form Group 1 (n=25) were administered orlistat at 120 mg x 3times a day for 6 month alongside with low-caloric diet and therapeutic physical exercise. Pts from Group 2 (n=25) adhered to life-modifying therapy only, i.e. low-caloric diet and therapeutic physical exercise for 6 month. Anthropometry data (height, body weight, BMI), as well as WOMAC and quality of life EQ-5D scores were assessed at baseline, at 6 and 12 months (i.e, 6 months after discontinuation of therapy) after initiation of treatment in all pts. Results: After 6 months of pharmacological therapy pts from Group 1 achieved significant mean weight loss by 10, 07% ( p <0, 05), while pts from Group 2 with non-pharmacological therapy demonstrated only <1% (0, 84%) (p>0, 05) weight loss. Pts receiving pharmacological therapy with orlistat demonstrated the following improvements by WOMAC subscales: pain reduction by 52, 5% (p<0, 05), stiffness reduction by 47, 98% ( p <0, 05), and 51, 55% function improvement, while total WOMAC score improved by 51, 49% ( p <0, 05). Respective WOMAC subscale scores in pts from Group 2 were considerably less impressive vs Group 1. Pts from Group 1 demonstrated statistically significant improvement in the quality of life by 52, 27% EQ-5D ( p <0, 05). EQ-5D score remained unchanged only in 2 pts from Group 1 who failed to lose weight. During the following 6 months after discontinuation of orlistat pts from Group 1 regained 5, 6% of their body weight ( p <0, 05) (Fig.1 ), which was associated with OA worsening OA (deterioration of pain by 42, 63% (p<0, 05) WOMAC, and total WOMAC score decrease by 23, 15%). After 12 months of follow up pts from Group 2 showed body weight loss by 3, 5%, and continuing decrease of pain in knee joints by WOMAC pain subscale, reaching 22, 3% (p <0, 05) as compared to baseline. Conclusions: The results of our study demonstrate significant >10% weight loss in OA pts induced by orlistat therapy. Such a noticeable weight loss was associated with reduced pain intensity, improved function and quality of life in OA pts. Partial regain of body weight during 6 months after discontinuation of orlistat was accompanied by worsening of OA clinical course. Thus, effective maintenance of optimal body weight in OA pts requires longer pharmacotherapy of obesity. Disclosure of Interest: None declared